The Role of Dopamine in Impulsivity and Substance Abuse: A Narrative Review - Connor J Plaisance; Lloyd F Ledet III; Nicholas J Slusher; Charles P Daniel; Zachary Lee; Bradley Dorius; Sonnah Barrie; Tomasina Q Parker-Actlis; Shahab Ahmadzadeh; Sahar Shekoohi; Alan D Kaye (Health Psychology Research)
Substance use disorder (SUD), based on the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), is defined by symptoms caused by utilizing a substance that a person continues taking despite its negative effects. Impulsive decision making is commonly defined as a reduced ability to choose a delayed large reward instead of a small immediate reward. Dopamine has been implicated as a prominent neurotransmitter implicated in the development and pattern of addiction and impulsivity, especially in regard to substance use disorder. Discovery as a key player in the development of addiction dates to the 1950s, with a study performed by Olds and Milner on rats placed in a Skinner box. Their original discovery is part of the beginning of what would become the search into the main mechanistic source of addiction, and how exactly it works at a cellular, physiological, and psychological level. The dopaminergic pathways of our brains are well-studied. It is well established that most of the dopaminergic neurons of the brain are located in the ventral mid-brain and consists of four main pathways: mesocortical, mesolimbic, nigrostriatal, and tuberoinfundibular pathways. Dopamine acts various receptors, with dopamine (D) receptors 1, 2, and 3 playing a major role in motor function and receptors D1 and D2 playing a major role in reward. There are additional studies warranted, especially finding ways to manipulate the dopaminergic system to treat addiction disorders of all varieties. The focus of the present investigation is to delve into the current literature regarding dopamine and its clinical implications in substance use disorder and impulsive behavior.